Gestión de servicio al cliente en el Almacén “Créditos Económicos” sucursal Babahoyo - Carbo Cabezas, Iliana Vanessa (2018)
Créditos Económicos was created in 1947 by Mr. Domingo Salame Hidrovo, in the city of Guayaquil, as a system to buy on credit, articles for home and personal use, in the year 1990 expansions of this company were made by Quito and Guayaquil. Créditos Económicos aims to facilitate the acquisition of products for the home, currently it is recognized at a national level, since the opening of a warehouse in the United States in the city of New York was implemented to serve Ecuadorians. branches distributed throughout the country: in Ambato, Guayaquil, Babahoyo, Manta, Machala, La Troncal among others